Globalized Antiquity: Uses and Perceptions of the Past in South Asia, Mesoamerica, and Europe - Schpren, Ute; Segesser, Daniel Marc; Späth, Thomas (Dietrich Reimer Verlag, 2015)
Inspired by post-colonial critics of the dominant Western canons in the fields of historiography, philology, cultural anthropology, and archaeology, this book explores the meanings and uses of “antiquity” in three cultural areas and compares the genealogies of the representations of their remote past. It discusses the entanglement of European conceptions of antiquity and its Mesoamerican and South-Asian appropriations and transformations. By diachronically exploring the functions of “antiquity”, the book provides cultural anthropology and post-colonial studies with historical foundations and implements the postulate of the local gaze at global phenomena for world history and globalization research.